Sonographic anatomy of the neck: The suprahyoid region - Gervasio, A. (Elsevier, 2011)
The suprahyoid region extends from the base of the skull to the hyoid bone and includes the pharyngeal, parapharyngeal, parotid, carotid, masticator, retropharyngeal, and perivertebral spaces, as well as the oral cavity. The areas that can be explored by ultrasound include the parotid, carotid, and masticator spaces; the oral cavity; the submandibular and sublingual spaces; the floor of the mouth; and the root of the tongue. The parotid space contains the parotid gland and the excretory duct of Steno, the facial nerve, the external carotid artery, the retromandibular vein, and the intraparotid lymph nodes. The carotid space in the suprahyoid region of the neck contains the internal carotid artery, the internal jugular vein, cranial nerves IX to XII, and the sympathetic plexus. Only some parts of the masticator space can be explored sonographically: these include the masseter muscle, the zygomatic arch and the outer cortex of the ramus of the mandible, and the suprazygomatic portion of the temporalis muscle. The submandibular space houses the submandibular gland, the submental and submandibular lymph nodes, and the anterior belly of digastric muscle. The facial artery and vein and the lower loop of the hypoglossal nerve all pass through the submandibular space. The sublingual space includes the sublingual gland, the deep portion of the submandibular gland and its main excretory duct, the hypoglossal nerve (cranial nerve XII), the lingual nerve (branch of the mandibular branch of trigeminal), and the glossopharyngeal nerve (IX cranial nerve), and the lingual artery and vein. The mylohyoid muscle forms the floor of the mouth. The deepest portion of the oral tongue, the root, consists of the genioglossus and geniohyoid muscles and includes the septum of the tongue. In this article we present the ultrasound features of the structures located in the suprahyoid region of the neck.